Clinical Findings in Healthy Dogs Fed With Diets Characterized by Different Carbohydrates Sources - Gizzarelli, Manuela; Calabrò, Serena; Vastolo, Alessandro; Molinaro, Giuseppe; Balestrino, Ines; Cutrignelli, Monica Isabella (Frontiers in Veterinary Science, 2021)
In recent years, pet owners have become more interested in the ingredients and quality of pet-food, and several studies have demonstrated that feed management could affect healthy status. Recently, some authors indicated that commercial diets formulated without cereals, or using unconventional protein and starch sources, can cause a reduction in taurine levels in both whole blood and plasma. Nevertheless, the specific mechanism by means of which nutritional factors determine this reduction is not completely clear. Thirty neutered half-breed dogs were recruited at a kennel in the province of Naples (Italy) to investigate the influence of carbohydrates sources and dietary density of nutrients on healthy status of dogs in terms of blood count and biochemical parameters. The dogs were housed in the kennel and divided into three distinct groups. Three iso-energy and iso-nitrogen commercial kibble diets (named GF1, GF2, and CB) with different protein and carbohydrates contents and carbohydrates sources were chosen for the trial. The chemical composition and amino acid profile of each of the three tested diets were analyzed. Moreover, blood samples of each dog were collected to evaluate the hematological and biochemical profiles. The taurine level was determined both on plasma and whole blood. The effect of the diets was analyzed statically, and all tested diets were compared to the control one. There were significant differences between the three tested diets as regards their chemical composition. The concentrations of all amino acids seem to reflect protein content diets. The hematological profile resulted within the ranges considered physiological for the canine species for all subjects. Compared to the control diet, the three tested diets showed significant differences in blood count for MCHC and platelets. The biochemical profile showed significant differences between the diets, particularly their AST, fructosamine, lipase, and triglycerides values. The diets did not affect the blood and plasma taurine levels. They resulted in higher than optimal reserve levels. Preliminary results showed that the sources of carbohydrates and use of balanced diets affected only some biochemical parameters and did not alter the levels of taurine in healthy adult dogs.